Coverage of chitosan and essential cinnamon oil for strawberry conservation (Fragaria ananassa) var. Aroma, minimally processed - Zavaleta, Magaly (2020)
ABSTRACT Abstract– The use of edible coverage represents one of the important methods used to preserve the quality of minimally processed products. The aim of this research was to determine the effect of chitosan and essential cinnamon oil coverage in the phenolic content, antioxidant capacity, mould and yeast count, and general acceptability in minimally processed strawberry along 16 days of refrigerated storage at 10 °C, in order to improve the conservation and characteristics of minimally processed strawberry var. aroma. In this experiment a response surface methodology using a Central Composite Rotational Design (CCRD) was carried out; the variable ranges used were 0.7 – 2% (Chitosan) and 0.02 – 0.1% (cinnamon essential oil). As results, it was found that the significant variable (p<0.05) was cinnamon essential oil for both phenols content and antioxidant capacity. For these characteristics, a concentration of 0.1% cinnamon essential oil was the most effective. The antioxidant capacity and phenolic contents showed an increase during the first 7 days of storage, decreasing after that for all treatments. It was also found that both independent variables significantly influence (p<0.05) in the decrease of microbial load being the optimal range of chitosan (1.33-1.71%) and cinnamon essential oil (0.056-0.087%). In addition, the use of coverage of chitosan and cinnamon essential oil does not negatively affect the sensory acceptability and helps to maintain the shelf life of minimally processed strawberry.